Decentralized Cloud Banking: Empowering Security and Efficiency with Blockchain, IPFS, and Smart Card Technology - Biswas, Ankur; Roy, Abhishek (International Journal of Intelligent Systems and Applications in Engineering, 2023)
ICT development has boosted the usage of electronic communications, especially during the COVID-19 epidemic, which has been advantageous for industries including banking, education, government, and healthcare. To safeguard sensitive messages from security risks, privacy, integrity, non-repudiation, and authentication (PINA) requirements must be upheld. Fraudulent financial transactions in the Indian banking industry have brought attention to the need for study into improving dependability and accountability. A safe and integrated electronic banking system using blockchain and IPFS for cloud banking is suggested to address flaws in electronic communication. To effectively evaluate security settings and resource allocation, simulations utilizing Object-Oriented Modelling (OOM) should be run. The importance of maintaining strong security measures in electronic banking and message transmission systems is emphasized in this study.